Perancangan Pengaduan Layanan Masyarakat Menggunakan Algoritma Priority Scheduling Di Kecamatan Teluk Segara Berbasis Website - Ibnu Nurul Mubaroq; Ujang Juhardi; Yulia Darmi (UNIVED Press, 2025)
The development of information technology today is quite advanced; however, this reality contrasts sharply with the services provided by government agencies, particularly those at the sub-district level. The sub-district government offices, which manage community services, need to update their quality, especially in the area of public complaint handling. Currently, it is still challenging for citizens to submit complaints about their local environment to the local government, which often results in residents directing their complaints to inappropriate channels. Therefore, the goal of this research is to design a web-based public complaint system for the Teluk Segara Sub-District Office, enabling citizens to more easily communicate their grievances to the relevant authorities.